Sosialisasi Sertifikasi Halal dan BPOM sebagai Upaya Mendorong Kepercayaan Konsumen: Studi Kasus Kelompok Usaha Bersama (KUB) Siabang - Destiartono, Mohamad Egi (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
This community service activity was conducted on 13 September 2025 in Asinan Village, Bawen District, Semarang Regency, involving the Kelompok Usaha Bersama (KUB) Siabang as the main partner. The program was organized by the Program Penguatan Kapasitas (PPK) Ormawa of the Student Executive Board (BEM), Faculty of Economics and Business, Universitas Diponegoro, with the objective of enhancing local entrepreneurs’ understanding and capacity in meeting product legality and safety standards. The activity primarily focused on disseminating information on Halal certification and the Badan Pengawas Obat dan Makanan (BPOM), including the requirements, procedures, and strategic benefits for small-business development. The results of the activity show an improvement in participants’ knowledge regarding the Halal certification and BPOM processes, which is expected to enhance the competitiveness of local products in broader markets.